Meso–Macro Coupled Analysis of Pressure-Dependent Friction of Rubber - Ozaki, Shingo; Mieda, Keishi; Maegawa, Satoru; Nakano, Ken (Frontiers in Mechanical Engineering, 2020)
To deepen the understanding of the frictional sliding phenomena of rough surfaces, advances are required in numerical analysis methods at various spatial scales. In this study, to examine the microscopic behavior of a rough asperity contact corresponding to a bulk contact on the macroscopic scale, a loop-type meso–macro coupled analysis scheme is proposed. A mesoscale numerical model and a macroscopic friction model are required for the proposed multi-scale analysis. A friction model was adopted based on the multipoint contact model for the mesoscale model, and the pressure- and state-dependent elastoplastic analogy friction model was used for the macroscale model. In the proposed meso¬¬–macro coupled analysis, the parameter set for the elastoplastic analogy friction model was first identified via a numerical friction test using the mesoscale multipoint contact model assuming various conditions. Then, a macroscale finite element analysis incorporating the elastoplastic analogy friction model was performed for the macroscopic analysis of contact between a rough rubber hemisphere and a smooth plate. Here, the information from the mesoscale rough surfaces were reflected in the macroscale finite element analysis. Finally, a mesoscale localization analysis was performed in which the macroscopic histories of several typical locations were obtained by finite element analysis and used as boundary conditions for the mesoscale model. It is suggested that the microscopic sliding process of rough surfaces represented by the finite element analysis can be examined using the proposed method.